Objetos de aprendizagem organizados como dados ligados interoperáveis na Web semântica: o reúso em evidência por meio de uma ontologia operacional - Alvarenga, Viviane Bessa Lopes (2023)
The amount of learning objects (LO) based on content developed for use in distance education has grown a lot due to the increased demand for courses in this modality. However, the development of these LOs, for the most part, are designed for a single platform, or are available in a repository without interoperability, which generates content redundancy, unnecessarily increases the cost of creation and maintenance, and going against its main feature, which is reusability. In this sense, new ways of organizing LOs have been investigated using standardized representation processes that enable access and reuse. One of the standards developed with the objective of organizing the LOs is the LOM (Learning Object Metadata) of the IEEE (Institute of Electrical and Electronics Engineers). Another element indicated in the representation of metadata and their relationships, with strong characteristics for reuse and interoperable access, is the domain operational ontology built in a context of linked data in the Semantic Web. Thus, the research problem is: how to use the LOM - IEEE standard to organize knowledge about LOs in order to improve their ability to be found, accessible, interoperable and reusable in linked open data environments? The general objective of the research is to create a domain operational ontology to help the organization of LOs in the LOM-IEEE standard considering the context of the Semantic Web. With a qualitative approach, applied nature and case study procedures, the research was developed in an organized way in eight procedural stages, in tune with the specific objectives, ranging from the investigation of learning object repositories, to the construction of the operational ontology and your test with the creation of a linked database and queries as a proof of concept. As research results, the adequacy of the LOM-IEEE standard for representing LOs stands out; a design model for the domain operational ontology; a domain operational ontology implemented in Turtle; the indication of interoperable elements of the structural and semantic layers; a mapping scheme for OAs RDF linked data; and information retrieval tests through SPARQL queries on the LO base. It is indicated, as a continuation of the research, the expansion and publication of the linked database of LOs, encompassing other repositories, and the development of an interface with good usability for queries to LOs, as well as its validation with a body of users.